Refleksi Praktik Pembelajaran Literasi Baca Anak Melalui Pelatihan Metode Read Aloud Bagi Pengelola Taman Baca Masyarakat Di Kota Metro - Uswatun Hasanah; Much Deiniatur; Revina Rizqiani; Dian Eka Priyantoro (Universitas Muhammadiyah Metro, 2023)
The aim of this research is to reflect on children's literacy learning practices through read-aloud method training for managers of community reading parks in metro cities. The method used is narrative inquiry. The instruments used were open questionnaires, interviews, and document analysis. The data analysis technique used is that, because this research is qualitative, the validity and reliability of the data need to be met. Thus, researchers use four criteria: credibility, transferability, dependability, and confirmability. The results of this research are that there is an increase in knowledge and skills, a positive impact on children's literacy, and increased collaboration in the community. Literacy activists are expected to be able to improve their competency in reading aloud through the training of trainers.